Hubungan Kepatuhan, Derajat Hipertensi dan Status Nutrisi: Obesitas dengan Defisiensi Vitamin D pada Pasien Hemodialisis : Compliance, Degree of Hypertension, and Nutritional Status: Obesity with Vitamin D Deficiency in Hemodialysis Patients - Nurjanah, Oktika; Susaldi; Sumedi (MPI Press, 2022)
Introduction: CKD (Chonic Kidney Disease) is a gradual failure of kidney function that causes the accumulation of metabolic waste substances (uremic toxins), resulting in decreased kidney function and gradual loss of kidney function over time. Objectives: To determine the relationship between adherence, degree of hypertension and nutritional status with vitamin d deficiency in hemodialysis patients. Method: The population of this study were all patients undergoing hemodialysis therapy in room 1 and room 2 of the Avio Prima Ciledug Hemodialysis Clinic, collecting 30 people. Sampling technique in this research is using total sampling technique. The number of samples in this study were 30 respondents. The research instrument used an observation sheet. This research uses chi square analysis. Result: The results of the study on the value of adherence to vitamin D intake obtained p-value = 0.003. Blood Pressure obtained p-value = 0.045. Nutritional status obtained p-value = 0.047. Conclusion: there is a relationship between the factors of age, type. There is a relationship between adherence to vitamin D intake, pressure, nutritional status and vitamin D deficiency in chronic disease patients undergoing hemodialysis.